The Concept of Islamic Education According to K.H. Ahmad Dahlan - Fitri, Adisty Nabilah; Sutarjo, Sutarjo; Karyawati, Lilis (Edumaspul: Jurnal Pendidikan, 2022)
This study discusses the concept of Islamic education according to K.H. Ahmad Dahlan. This study analyzes the thoughts of KH. Ahmad Dahlan who has designed the concept of Islamic education completely and perfectly without separating general education from Islamic education. This research uses qualitative research, with the type of literature research, with data collection techniques, namely by digging library materials such as books, journals, articles, and other materials. From the results of this study, it was found that the concept of Islamic education according to KH. Ahmad Dahlan is an education that is able to integrate general knowledge with religion, maintain balance, has an intellectual, moral and religious character.